POTENSI OBJEK WISATA AIR TERJUN LUBUAK TAMPURUANG KECAMATAN KURANJI KOTA PADANG. - aizil ikhsan pratama; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to determine the potential tourist attraction of Lubuak Tampuruang Waterfall from its attractiveness, for the potential of Lubuak Tampuruang Waterfall's tourist attraction from tourism accessibility, for the potential of Lubuak Tampuruang Waterfall's tourist attraction from tourism facilities and infrastructure and management. The type of research used is descriptive with a qualitative approach. This research was conducted in December 2021 at Lubuak Tampuruang Waterfall. The subjects in this study were taken by snowball by interviewing informants related to the Lubuak Tampuruang Waterfall tourist attraction by involving the Belimbing Village Head, local RW, local RT, Parker guards, shop owners and visitors. Data collection techniques in this study were observation, interviews and documentation. The data analysis technique uses data reduction and display techniques. The results of the research on the development of the Lubuak Tampuruang Waterfall tourism object can be concluded: 1) The attraction of this tourist attraction is the scorching power of natural attractions, namely waterfalls and the absence of artificial tourist attractions 2) in terms of the accessibility of the tourist attraction is still not constrained. there is cooperation from the government, so that the road to the tourist attraction is still a dirt road mixed with gravel, there has been no road repair along the road to the tourist attraction, while the Lubuak Tampuruang Waterfall is easily accessible by visitors because the distance from the city center is about 14 km. 3) judging from the facilities and infrastructure there is no assistance from the government to fix and facilitate facilities to help visitors to tourist attractions, the availability of parking lots made by the community, but the conditions are not too good and there are no directions on each route to the waterfall 4) the management is carried out by means of road construction planning by the government in 2013 but until now this has not been implemented and this tourist attraction is only managed by the local community